Penerapan Akuntansi Pertanggungjawaban Sebagai Alat Pengendalian Biaya Pada RSUD Kab Buleleng - Ni Kadek Herlinda Ayu Wandari; Edy Sujana (Universitas Pendidikan Ganesha, 2021)
The study aims to find out how the implementation of the Accounting centre accountability fee has been implemented by the District Hospital of Buleleng and to find out how the accounting benefits the cost center accountability as a hospitals performance assessment tool. The results of the analysis that the RSUD of Buleleng Regency, Bali has implemented accounting accountability as a tool of cost control well and according to the rules. There is an organizational structure that clearly implements the authority and responsibility of each management level, the budget preparation process refers to a one-year hospital plan, the separation of controlled and uncontrolled costs, the classification of the account code, as well as the cost reporting system as a condition of application of accountability accounting. But on the reporting system, the format of hospital accountability report is different from theory. This is because the hospital is a type of BLUD where in the reporting is always posted in the application so that the format of the accountability report must comply with government-defined regulations. All the difference between the budget and the realization of the cost of oprational shows the difference of favourable (profitable).